v.7 - "Keynes, John Maynard" (New Delhi, 2013)
In 1936 Keynes published the most provocative book written by any economist of his generation. The General Theory, as it is known to all economists, cut through all the Gordian Knots of pre-Keynesian discussion of the trade cycle and propounded a new approach to the determination of the level of economic activity, the problems of employment and unemployment and the causes of inflation. Arguments about the book continued until his death in 1946 and still continue today. Despite all that has been written in the subsequent years, Keynes and his book still represent the turning point between the old economics and the new from which each generation of economists needs to take its inspiration.
Keywords: Keynesianism